A randomized controlled trial to compare the percentage of glottic opening score of McGrath MAC® video laryngoscope and C-MAC® video laryngoscope in children - Ranju Singh; K Manikandan; Pooja Singh (The Indian Anaesthetists' Forum, 2025)
Background and Aims: Video laryngoscopes (VL) have now an established role in the management of difficult airway. The design of VL blade may affect the tracheal intubation outcomes. This study compares the percentage of glottic opening (POGO) score of McGrath MAC® VL with C-MAC® VL in children. Materials and Methods: Ninety-four children, between 1 and 10 years, belonging to ASA-I and II were randomized into two groups. After induction, Group I was intubated with McGrath MAC® VL and Group II with C-MAC® VL. The POGO score, application of external laryngeal manoeuver, POGO score after the application of optimal external laryngeal manoeuver (OELM), number of attempts at laryngoscopy, time for best glottic view, time taken for intubation, number of attempts at intubation, ease of intubation, hemodynamic changes, and complications were recorded. Results: The number of patients with POGO score ≥5 was more in the Group II (100% vs. 93.6%, P = 0.025) than Group I. The number of patients requiring application of OELM to achieve POGO score ≥5 were more in Group I than Group II (19.1% vs. 2.1%, P = 0.015). With C-MAC® VL, less time was required to obtain the best glottic view and also for tracheal intubation and it resulted in less hemodynamic response as compared to McGrath MAC® VL. Attempts at laryngoscopy and intubation, ease of intubation, and complications were the same in both the groups. Conclusion: The C-MAC® VL may be preferred over McGrath MAC® VL for airway management in children between 1 and 10 years of age in view of lesser time to best glottic view and intubation.